Extraskeletal versus Skeletal Ewing Sarcoma in the adult population: Controversies in care. (September 2018) - Lynch, Andrew D.; Gani, Faiz; Meyer, Christian F.; Morris, Carol D.; Ahuja, Nita; Johnston, Fabian M.
Abstract: Background and Objectives: A lack of consensus exists on the prognosis of extraskeletal Ewing sarcoma (EES) relative to its skeletal (ES) counterpart in adults. This study sought to characterize outcome differences between the two diagnoses. Methods: From 2004 to 2014, the NCDB identified 2, 660 Ewing Sarcoma patients. Cox proportional hazards regression analysis was used to identify risk factors for overall survival (OS). Results: EES patients were older, more likely to be female, and have smaller tumors. Among patients with ES, 4.0% received no treatment, 2.5% received local therapy only (surgery and/or radiation), 16.8% received chemotherapy only, while 52.2% received combination therapy (local and chemotherapy), and 17.0% recieived triple therapy (surgery, radiation and chemotherapy). Among patients with EES, 4.3% recived no treatment, 5.6% received local therapy only, 15.6% received chemotherapy only, while 47.0% received combination therapy, and 21.6% received triple therapy. No difference in OS was observed between the two groups (P = 0.816). Factors independently associated with OS for ES included age (HR = 1.26, P = 0.01), Charlson-Deyo Score (CDS) ≥2 (HR = 3.66, P < 0.001), combination therapy (HR = 0.39, P < 0.001) and triple therapy (HR = 0.34, P < 0.001). For EES, factors for OS were age (HR = 1.52, P < 0.001), CDS ≥2 (HR = 1.90, P = 0.02), combination therapy (HR = 0.44, P < 0.001), triple therapy (HR = 0.34, P < 0.001) and PNET histology (HR = 1.33, P = 0.02). Conclusions: Demographic, histological, and treatment characteristics differ between adult patients diagnosed with ES and ESS. However, survival and independent predictors of survival are consistent between the two diagnoses.